Soros Conference at MTA - Part 2
Part II. Conference at MTA (Hungarian Academy of Science) where the participants debate George Soros’ article “The Capitalist Threat”. Introduction offered by George Soros. Arguments discussed by András Brody (Hungarian Academy of Sciences), Olivier Giscard d’Estaing (Business Association for the World Social Summit, Paris), Ferenc Rabár (Budapest University of Economic Sciences) and Jörn Rüsen (Kulturwissenschaftliches Institut, Essen). The hosts of the event were Prof. Sorin Antohi (CEU Academic Pro-Rector), Prof. András Nemeslaki (MBA Director and Associate Dean, International Management Center) and Prof. László Zsolnai (Director, Business Ethics Center, Budapest University of Economic Sciences).